Local administration of stem cell-derived extracellular vesicles in a thermoresponsive hydrogel promotes a pro-healing effect in a rat model of colo-cutaneous post-surgical fistula. Issue 1 (16th December 2020) - Berger, Arthur; Araújo-Filho, Irami; Piffoux, Max; Nicolás-Boluda, Alba; Grangier, Alice; Boucenna, Imane; Real, Caroline Cristiano; Marques, Fabio Luiz Navarro; de Paula Faria, Daniele; do Rego, Amália Cinthia Meneses; Broudin, Chloe; Gazeau, Florence; et al.
Abstract : Local minimally-invasive EV delivery on a thermo-actuated PF-127 gel enhanced EV residence time in colo-cutaneous fistulas promoting a therapeutic effect. Abstract : Extracellular vesicles (EVs), especially from stem/stromal cells (SCs), represent a cell-free alternative in regenerative medicine holding promises to promote tissue healing while providing safety and logistic advantages in comparison to cellular counterparts. Herein, we hypothesize that SC EVs, administered locally in a thermoresponsive gel, is a therapeutic strategy for managing post-surgical colo-cutaneous fistulas. This disease is a neglected and challenging condition associated to low remission rates and high refractoriness. Herein, EVs from a murine SC line were produced by a high-yield scalable method in bioreactors. The post-surgical intestinal fistula model was induced via a surgical cecostomy communicating the cecum and the skin in Wistar rats. Animals were treated just after cecostomy with PBS, thermoresponsive Pluronic F-127 hydrogel alone or containing SC EVs. A PET-monitored biodistribution investigation of SC EVs labelled with 89 Zr was performed. Fistula external orifice and output assessment, probe-based confocal laser endomicroscopy, MRI and histology were carried out for therapy follow-up. The relevance of percutaneous EV administration embedded in the hydrogel vehicle was indicated by the PET-biodistribution study. Local administration of SC EVs in the hydrogel reduced colo-cutaneous fistula diameter, output, fibrosis and inflammation while increasing the density of neo-vessels when compared to the PBS and gel groups. This multi-modal investigation pointed-out the therapeutic potential of SC EVs administered locally and in a thermoresponsive hydrogel for the management of challenging post-surgical colon fistulas in a minimally-invasive cell-free strategy.